Ultrasonic imaging of buried defects in rails. (January 2023) - Rodriguez, Samuel; Gayoux, Victor; Ducasse, Eric; Castaings, Michel; Patteeuw, Nicolas
Abstract: The present work addresses the ultrasonic NDT of rails, more precisely of the rail foot. The practical constraint is that transducers must be located on the rail head, whereas the region of interest is the rail foot. Thus, there is no direct acoustic path between the transducers and the region of interest. As classical delay and sum methods cannot be applied to such cases, the goal of the paper is to numerically assess the potentiality of the topological imaging method to investigate the rail foot. Three specific typical rail foot defects are investigated, namely, longitudinal vertical cracks, corrosion pits and rail injuries. Simulating eight transducers with different polarizations, the images obtained show that the detection and approximate location of the various defects are possible. Highlights: Topological imaging is numerically assessed for rail foot NDT. The Laplace-domain numerical model is experimentally validated. Typical rail foot defects are successfully located using rail head transducers. Time-truncation of long-lasting reverberated measurements allows defect location.